EFFECT OF HEATING AND STORAGE TIME LEVELS 5- (Hydroxy Methyl) furan-2- KARBALDEHIDA (HMF) IN HONEY ORIGIN MALLAWA - Suhaela Suhaela; Alfian Noor; Ahyar Ahmad (Marina Chimica Acta, 2016)
A research has been on determining the origin of forest honey quality Mallawa Maros based on the levels of 5-(hydroxymethyl)furfural-2-karbaldehida (HMF)is quantitatively based on the variation of heating temperature and duration of storage with White spectrophotometric method. The results showed that the levels of forest honey HMF origin Mallawa on heating temperature 35°C,90°C and 110°C respectively is 42.2023 mg/Kg, 46.0274 mg/Kg and 62.2520 mg/Kg. While the storage duration for 3,4, and 5 months had higher levels of HMF each 27.4309 mg/Kg, 42.5158 mg/Kg and 48.9405 mg/Kg. Heating temperature and storage time a big influence on levels of HMF and show a strong relationship to the water content, pH and free acid, reducing sugar content and diastase enzyme activity. Based on the research results, levels of HMF at the heating temperature of 110oC has passed the standards set by the SNI (up to 50 mg/Kg). Whereas the standard set by IHC for honey originating from thetropics (80 mg/ Kg)